Consequences of Inadequate Management of Personnel Information in a SME enterprise - Viera SUKALOVA (Communications of International Proceedings, 2023)
If an organization wants to be successful, it is very important to realize the value of human capital and the importance of the people it employs; people in an organization are considered the greatest wealth and their management depends on whether the organization succeeds in the market or not. Personnel functions can be performed based on correct information, and this is what the personnel information system is for; every decision-making process takes place through information. That is why it is important to have information. Decision-making in the field of human resources management is conditioned using appropriate personnel information. This is information that should be: true, accurate, up-to-date, relevant, and sufficiently detailed. With the aim of effective functioning of the organization, effective management and decision-making, compliance with obligations arising from legal regulations and regulations, it is necessary for every organization to pay attention to the compilation of a personnel information system. It is an organized computer system that detects, processes, provides and stores all information about personnel work in the enterprise. It is created by a network of data, databases, tools, and services in the field of human resources. The goal of our research was to analyse the state of the personnel information system on the example of an industrial enterprise, to identify shortcomings and their impact on employee satisfaction and the perception of managers. The methods used were analysis, synthesis, deduction, questioning in the form of interview and questionnaire.
Keywords: management; information; system; human resources